Insights into Community Attitudes and Perceptions at Borakalalo National Park, South Africa. (November 2021) - Gordon-Cumming, Ian; Mearns, Kevin
Meaningful community participation is core to the long-term success of protected areas. Hence, it is important to understand what drives neighbouring community attitudes and perceptions. This study sought to determine local community attitudes towards conservation and protected areas, as well as their perceptions of benefits and participation at Borakalalo National Park. Semi-structured interviews were held with experienced park officials, while a structured household survey and focus group discussions were conducted across five surrounding villages. The results highlighted a number of interesting findings, including widespread support for biodiversity conservation and protected areas offset by considerable negativity towards Borakalalo itself. It was also determined, despite stated co-management policies, community residents perceived there was little meaningful participation and benefits were poorly communicated and unfairly distributed. Pragmatic suggestions were made for jointly developing more effective participation with the communities, despite limited available resources.